Comparison of peripheral sudomotor sensitivity to acetylcholine in endurance and non-endurance trained male subjects - Shin, Young Oh; Lee, Jeong Beom (Muscle & nerve, 2014)
ABSTRACT Introduction: We investigated the effect of endurance and non‐endurance training on peripheral sudomotor sensitivity. Methods: The quantitative sudomotor axon reflex test (QSART) was performed. Results: Endurance‐trained subjects (ET, long‐distance runners) had a significantly shorter onset time of sweating, greater sweat volume, increased density of activated sweat glands and sweat gland output per single activated gland, greater volume of transepidermal water loss, and higher skin temperature compared with those in the other 2 groups [non–endurance‐trained group (NET), sedentary control group (CT)]. NET subjects (baseball players) had a tendency to increase in these variables; thus, some values were greater than control subjects. Conclusions: These results suggest that endurance training much more effectively modifies sudomotor sensitivity than non‐endurance training. Muscle Nerve 50: 407–412, 2014